Influence of weather variables on leafhopper, Empoasca flavescens population in selected castor genotypes - Narayanamma, V Lakshmi (Indian Journal of Plant Protection, 2020)
Field experiments were conducted to study the seasonal incidence and influence of weather variables on the population of leafhopper, Empoasca flavescens in eight genotypes of castor during 2008-13 Rabi season and weather based pest forewarning models were developed using regression models. The incidence started on the leaves during 43rd standard week with the peak incidence during 5th to 7th standard weeks, while the incidence was less after 8th standard week. Among the eight genotypes DCH-177 and DPC-9 were more preferred by the pest while GCH-4 was least preferred. Correlation co-efficient studies revealed significant negative influence of all the weather parameters except evaporation. Minimum temperature did not show significant influence on leafhopper incidence in all the genotypes except in PCH-111. Weather based pest forewarning models developed for eight genotypes of castor for leafhopper explained the variation in hopper population by 33 to 52 per cent with linear models as compared to 38 to 71 per cent obtained with non linear models. Prediction models developed indicated that non linear regression equations predicted the pest incidence with higher precision than linear regression.